Driving Change: The Role Of Local Government In Enhancing Human Development Index In Ambon - Leonila Chrisanty Natalie Teniwut; M. Irwan Tahir (Maneggio, 2024)
Problem/Background (GAP): Unemployment in Indonesia is a complex problem; the high number of unemployed people has an impact on the high demand for labor. This problem can be caused by various factors, such as slow economic growth, a mismatch between labor qualifications and market demand, and changes in economic structure.  Objective: To find out how much local government performance affects the increase in the human development index and unemployment rate. Method: the research that researchers use is descriptive quantitative method and inferential statistics. Researchers in conducting this research used secondary data. Results: Parametric data is a form of secondary data where this parametric data uses time series with existing data. Local government performance has a positive effect on the unemployment rate. Local government performance shows a positive relationship to the Human Development Index (HDI) seen from the t-test with the results showing at 5% alpha coefficient (t-stat=18.79279>1.833). The result of sobel test shows that there is a moderating effect of the intervening variable (HDI) to the Local Government Performance on the Unemployment Rate, it is shown by the P-value of 0.2518 (<0.05). Conclusion: The existence of local government performance has a significant influence in increasing the human development index and decreasing the unemployment rate.